2006
DOI: 10.1128/aem.01388-06
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Accumulation of Trehalose Protects Lactococcus lactis from Freeze-Drying Damage and Bile Toxicity and Increases Gastric Acid Resistance

Abstract: Interleukin-10 (IL-10) is a promising candidate for the treatment of inflammatory bowel disease. Intragastric administration of Lactococcus lactis genetically modified to secrete IL-10 in situ in the intestine was shown to be effective in healing and preventing chronic colitis in mice. However, its use in humans is hindered by the sensitivity of L. lactis to freeze-drying and its poor survival in the gastrointestinal tract. We expressed the trehalose synthesizing genes from Escherichia coli under control of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 48 publications
4
44
2
1
Order By: Relevance
“…In any case, improved survival of the complemented strain in gastric juice containing added betaine suggests that it is the compatible solute (accumulated via BetL) that is responsible for the observed increased tolerance to the gastric juice. Interestingly, in support of this observation Termont et al (2006) recently reported improved tolerance to gastric juice in a Lactococcus lactis strain expressing trehalose-synthesizing genes from E. coli, suggesting a protective role for compatible solutes in the gastric environment.…”
Section: Discussionmentioning
confidence: 50%
“…In any case, improved survival of the complemented strain in gastric juice containing added betaine suggests that it is the compatible solute (accumulated via BetL) that is responsible for the observed increased tolerance to the gastric juice. Interestingly, in support of this observation Termont et al (2006) recently reported improved tolerance to gastric juice in a Lactococcus lactis strain expressing trehalose-synthesizing genes from E. coli, suggesting a protective role for compatible solutes in the gastric environment.…”
Section: Discussionmentioning
confidence: 50%
“…Similarly, cloning of the trehalose synthesis gene (ostAB) from E. coli into Lactococcus lactis protected recombinant bacteria from freeze-drying, bile toxicity, and resistance to gastric acid. 59 Furthermore, cloning of betL into Bifidobacterium breve UCC2003 significantly improved its survival in gastric juice thus improving its therapeutic attributes. 60 …”
Section: Bioengineering Of Probiotics To Improve Stress Tolerancementioning
confidence: 99%
“…However, the use of bacteria in humans is hampered by the susceptibility to the lyophilization process and bacterial death within the gastrointestinal tract (GIT). In this context, more efficient means of delivery at the mucosal level for therapeutic lactic bacteria are being developed [10][11][12].…”
Section: Editorialmentioning
confidence: 99%